2016
DOI: 10.1038/labinvest.2015.168
|View full text |Cite
|
Sign up to set email alerts
|

A selective screening platform reveals unique global expression patterns of microRNAs in a cohort of human soft-tissue sarcomas

Abstract: Sarcomas are malignant heterogenous tumors of mesenchymal derivation. Emerging data suggest that miRNA might have a causal role in sarcomagenesis. Herein, we used a selective miRNA screening platform to study the comparative global miRNA expression signatures in a cohort of human sarcomas with the caveat that comparisons between tumor and non-tumor cells were performed from the same patients using formalin-fixed paraffin-embedded tissue. Five histologic types were examined that included: myxoid liposarcoma, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…On the contrary, miR-143, miR-145 and miR-451, molecules with tumor suppressor properties in LPS [23, 35, 36], are clearly downregulated in LPS compared to LPM tissue specimens (Figure 2), corroborating the results of previously published studies [23, 24, 35, 36, 48, 50]. MiR-143 inhibits proliferation, induces apoptosis and cytokinesis of dedifferentiated liposarcoma cells by lowering BCL2 , TOP2A , PRC1 and PLK1 expression [36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the contrary, miR-143, miR-145 and miR-451, molecules with tumor suppressor properties in LPS [23, 35, 36], are clearly downregulated in LPS compared to LPM tissue specimens (Figure 2), corroborating the results of previously published studies [23, 24, 35, 36, 48, 50]. MiR-143 inhibits proliferation, induces apoptosis and cytokinesis of dedifferentiated liposarcoma cells by lowering BCL2 , TOP2A , PRC1 and PLK1 expression [36].…”
Section: Discussionsupporting
confidence: 90%
“…MiR-21 and miR-155 two of the most repeatedly reported upregulated miRNAs in LPS [23–26, 48] were also found to be robustly upregulated in our study and could efficiently discriminate LPS and LPM specimens with high specificity and sensitivity (Figure 2). Interestingly, a recent study by Boro et al showed that circulating levels of miRNA-155 in LPS patients correlate strongly with corresponding tissue levels.…”
Section: Discussionsupporting
confidence: 66%
“…To date, miRNA dysregulation in SS cells or tissue specimens has been reported by several groups (Supplementary Table S7 ) 13 18 . The representative functional miRNAs in SS cells includes the upregulated miR-17-5p 18 , miR-99b , miR-125a 15 , miR-183 17 , and the downregulated miR-143 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Low expression of miR-145 in pleomorphic RMS, liposarcoma and synovial sarcoma was observed. Muscle-specific miR-133, miR-1 and miR-206 are expressed lower in liposarcoma and synovial sarcoma, indicating they may act as tumor suppressors in these tumors [78] . In addition, recent studies have employed qRT-PCR for osteosarcoma research.…”
Section: Mirna Analysismentioning
confidence: 99%